2020
DOI: 10.3390/jcm9041004
|View full text |Cite
|
Sign up to set email alerts
|

Axonopathy and Reduction of Membrane Resistance: Key Features in a New Murine Model of Human GM1-Gangliosidosis

Abstract: GM1-gangliosidosis is caused by a reduced activity of β-galactosidase (Glb1), resulting in intralysosomal accumulations of GM1. The aim of this study was to reveal the pathogenic mechanisms of GM1-gangliosidosis in a new Glb1 knockout mouse model. Glb1−/− mice were analyzed clinically, histologically, immunohistochemically, electrophysiologically and biochemically. Morphological lesions in the central nervous system were already observed in two-month-old mice, whereas functional deficits, including ataxia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 123 publications
0
26
0
Order By: Relevance
“…With the development of new gene editing approaches, additional β-gal deficient mouse models have been more recently generated using either TALEN or CRISPR/Cas9 technologies (Przybilla et al, 2019;Eikelberg et al, 2020;Liu et al, 2021). Using CRISPR/Cas9 Przybilla et al (2019) engineered a knockout mouse model by introducing a deletion in exon 8 of the Glb1 gene.…”
Section: (See Below)mentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of new gene editing approaches, additional β-gal deficient mouse models have been more recently generated using either TALEN or CRISPR/Cas9 technologies (Przybilla et al, 2019;Eikelberg et al, 2020;Liu et al, 2021). Using CRISPR/Cas9 Przybilla et al (2019) engineered a knockout mouse model by introducing a deletion in exon 8 of the Glb1 gene.…”
Section: (See Below)mentioning
confidence: 99%
“…Phenotypic alterations in these mice were evaluated using behavioral tests that showed profound neurocognitive impairment (Przybilla et al, 2019). In Eikelberg et al (2020) described a knock-out model using TALENs to target exon 15 of Glb1. These mice display brain and spinal cord pathology, characterized by swelling of axons and loss of myelin, leading to abnormal electrophysiological activity of neurons (Eikelberg et al, 2020).…”
Section: (See Below)mentioning
confidence: 99%
See 1 more Smart Citation
“…GM1 gangliosidosis mouse models have been generated through knockout of the glb1 gene and complete loss of β-gal activity. [50][51][52][53] Gross abnormalities are absent in mice until about 4-5 months of age, at which point, affected mice develop severe clinical signs including tremor, ataxia, and abnormal gait. 50,52 In the recent literature, a CRISPR/Cas-generated 20 bp deletion in exon 8 of glb1 produces a GM1 mouse that reaches humane endpoint at 7-10 months with no detectable β-gal activity.…”
Section: Diagnosismentioning
confidence: 99%
“…Consequently, G M1 ‐gangliosides and related glycoconjugates are deposited in several tissues but especially within neurons 37 . This leads to distension with subsequent death of neurons within both, CNS and PNS 37,40,41 . Studying murine models for G M1 ‐gangliosidosis, it was observed that Glb1‐deficient mice, despite increasing accumulations of G M1 ‐ganglioside, did not show clinical abnormalities up to the age of 4–5 months 35,42 …”
Section: Introductionmentioning
confidence: 99%